The Influence of Intrapersonal Constraints on Travel Intention of People at High Risk from COVID-19 during the New Normal - Widiyastuti, Dyah; Wardhani, Ikasari Kusuma (UI Scholars Hub, 2022)
Due to the COVID-19 pandemic, tourism constraints have created a challenge for inclusive tourism, especially for older people and people with comorbidities. This study examined intrapersonal constraints’ effect on the travel intentions of people facing fewer opportunities for tourism due to the COVID-19 pandemic, which could disrupt their well-being fulfillment. The data were collected through an online survey of Jakarta citizens aged 46 years and older from the end of June to September 2021, and a total of 337 responses were accumulated. This study applied partial least square structural equation modeling to test the moderating effect of intrapersonal constraints toward the theory of planned behavior and revealed that the travel intentions of people at high risk from COVID-19 were considered high and were directly influenced by subjective norms, perceived behavioral control, and intrapersonal constraints. High travel intention implies that intrapersonal constraints do not extensively weaken at-risk people’s desire to travel during the new normal.